Biology of Rhodococcus - Alvarez, Héctor M. (Microbiology Monographs, 2010)
Rhodococcus, a metabolically versatile actinobacteria which is frequently found in the environment, has gained increasing interest due to its potential biotechnological applications. This Microbiology Monographs volume provides a thorough review of the various aspects of the biochemistry, physiology and genetics of the Genus Rhodococcus. Following an overview of its taxonomy, chapters cover the structural aspects of rhodococcal cellular envelope, genomes and plasmids, metabolic and catabolic pathways, such as those of aromatic compounds, steroids and nitriles, and desulfurization pathways, as well as the adaption to organic solvents. Further reviews discuss applications of Rhodococcus in the bioremediation of contaminated environments, in triacylglycerol accumulation, and in phytopathogenic strategies, as well as the potential of biosurfactants. A final chapter describes the sole pathogenic Rhodococcus member, R. equi.